2022
DOI: 10.3390/ma15217723
|View full text |Cite
|
Sign up to set email alerts
|

Grinding Temperature and Surface Integrity of Quenched Automotive Transmission Gear during the Form Grinding Process

Abstract: Grinding burn is an undesired defect in gear machining, and a white layer is an indication of severe burn that is detrimental to gear surface performance. In this work, the influence of grinding parameters on the thickness of the white layer during form grinding of quenched transmission gear was investigated, and the microstructure evolution and mechanism of severe burn formation were analyzed. The grinding temperature increased with the grinding depth and grinding speed, with the highest level of ~290 °C. The… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 12 publications
(6 citation statements)
references
References 34 publications
0
6
0
Order By: Relevance
“…The sample surface topography analysis after grinding indicates that during machining, furrowing of the machined material was observed ( Figure 4 ). This is characteristic of the grinding process in a plastic flow situation [ 55 ]. The observed surfaces do not show defects over large areas, which is characteristic of brittle fracture mechanisms.…”
Section: Resultsmentioning
confidence: 99%
“…The sample surface topography analysis after grinding indicates that during machining, furrowing of the machined material was observed ( Figure 4 ). This is characteristic of the grinding process in a plastic flow situation [ 55 ]. The observed surfaces do not show defects over large areas, which is characteristic of brittle fracture mechanisms.…”
Section: Resultsmentioning
confidence: 99%
“…By comparing the cross-section profile of the ground surface, it can be found that the CBN wheel grinding surface profile was smooth, while the alumina wheel grinding surface profile was rough, including short lines, bumps, and pits. In addition to the pits, it can also be observed that a bright white dense layer on the surface ground by the alumina wheel, which was similar to the plastic deformation layer caused by mechanical extrusion [ 23 ]. The surface material was crushed into smaller grains under the extrusion of the grinding wheel, so the structure became relatively dense.…”
Section: Resultsmentioning
confidence: 99%
“…The allowance in P3 was divided into three stages, with a grinding depth of 0.025 mm in the rough grinding stage (14 passes), 0.015 mm in the semi-fine grinding stage (2 passes), and 0.01 mm in the fine grinding stage (2 passes). As the grinding depth increased, more abrasive particles were involved in the cutting process, generating and transferring more heat into the workpiece [ 20 , 21 , 22 ]. Additionally, the limited thermal conductivity of the workpiece material and the limited time interval between each grinding stroke led to heat accumulation.…”
Section: Resultsmentioning
confidence: 99%